Multinational Banks in Regulated Markets: Is Financial Integration Desirable? - Andreas Haufler; Ian Wooton (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
We set up a two-country, regional model of trade in financial services. Competitive firms in each country manufacture non-traded consumer goods in an uncertain productive environment, borrowing funds from a bank in either the home or the foreign market. Duopolistic banks can choose their levels of monitoring of firms and thus the levels of risk-taking, where the risk of bank failure is partly borne by taxpayers in the banksh́ome countries. Moreover, each bank chooses the allocation of its lending between domestic and foreign firms, while the bankś overall loan volume is fixed by a capital requirement set optimally in its home country. In this setting we consider two types of financial integration. A reduction in the compliance costs of cross-border banking reduces aggregate output and increases risk-taking, thus harming consumers and taxpayers in both countries. In contrast, a reduction in the costs of screening foreign firms is likely to be eneficial for banks, consumers, and taxpayers alike.
Keywords: F36; G18; H81; 330; multinational banks; foreign direct investment; capital regulation; financial integration